The effect of health promotion based on audiovisual media on man’s contraception used in rural areas : A quasi-experimental study - Khasanah, Nur; Vidayanti, Venny; Liliana, Anita; Wahyuningsih, Melania (Jurnal Kebidanan Indonesia, 2024)
Background: The user of male contraceptives in Indonesia very low (6.34%), included Special Region of Yogyakarta is only (9.34%). The multifactorial causes, there are knowledge, awareness and interested of contraceptives. Its very important to increase the use of male contraceptives by professional contribution by health promostion. Objective: Determined the influence of education-based education audiovisuals on men's knowledge, awarness, and interested of contraception in Nglanggeran Patuk Yogyakarta. Method: This research used Quasi-Experiment with pre and post-test design without control (control self). Study was conducted between June and July 2023 using Quistionare. The intervention was given 2 session health promotion based on Informational by audiovisual media, then motivation and behaviour skill (IMB) model on contraceptive use among male.The sample size is 40 respondents collected by total sampling technique, data analysis was done using SPSS softwere version 22 with Wilcoson's test with significant level of P<0,005 was used. Results: Knowledge before education was sufficient for 23 (57.5%) and 36 (90.0%) after good knowledge education with a p-value of 0.00. awarness before positive awarness education 39 (97.5%) and after positive awarness education 40 (100%), with a p-value of 0.00. Interest before education moderated at 22 (55.0%), and after high-interest education, at 35 (87.5%), with a p-value of 0.00. Condoms dominate the selection of contraceptives before and after education. Conclusion: It was found that health promotion based on audiovisual media was effective in increase men's knowledge, creating awarness and interest in contraception use